Epidemiology and Etiology Of Bleeding Gastrointestinal Tract at Cut Meutia General Hospital North Aceh 2019-2021 - Muhammad Sayuti; Irfanul Aulia (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Gastrointestinal tract is a condition in which bleeding occurs in the oesophagus, stomach, duodenum, jejunum, ileum, and rectum. This is caused by many things, such as in the upper gastrointestinal tract due to gastric ulcers, various esophageal ruptures, Mallory Weiss syndrome, esophagitis, and tumors. While the lower gastrointestinal tract can be caused by Crohn's disease, ulcerative colitis, diverticulitis, intestinal polyps, anal fissures, hemorrhoids and tumors. The description of age characteristics at the time of gastrointestinal bleeding at Cut Meutia General Hospital, North Aceh Regency in 2019- 2021 was mostly at the age of 20 - 34 years, which found 17 people (28.7%). Description of the characteristics by gender in the female gender recorded 42 people (65.5%). The number of patients who underwent endoscopy at Cut Meutia General Hospital, North Aceh Regency in 2019-2021 presented 73 people of whom 59 people underwent colonoscopy (77.5%) and 14 people who underwent gastroscopy (22.5%).